2003
DOI: 10.1046/j.1432-1033.2003.03594.x
|View full text |Cite
|
Sign up to set email alerts
|

The histidine‐phosphocarrier protein ofStreptomyces coelicolorfolds by a partially folded species at low pH

Abstract: The folding of a 93-residue protein, the histidine-phosphocarrier protein of Streptomyces coelicolor, HPr, has been studied using several biophysical techniques, namely fluorescence, 8-anilinonaphthalene-1-sulfate binding, circular dichroism, Fourier transform infrared spectroscopy, gel filtration chromatography and differential scanning calorimetry. The chemical-denaturation behaviour of HPr, followed by fluorescence, CD and gel filtration, at pH 7.5 and 25°C, is described as a two-state process, which does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 58 publications
6
41
0
Order By: Relevance
“…3). The spectra are identical with each other and the ones of E. coli and Streptomyces coelicolor HPr (23,24). We therefore assume that all proteins are correctly folded.…”
Section: Hpr-ser46-p and Crh-ser46-p Mutants With Changes In Residuesmentioning
confidence: 99%
“…3). The spectra are identical with each other and the ones of E. coli and Streptomyces coelicolor HPr (23,24). We therefore assume that all proteins are correctly folded.…”
Section: Hpr-ser46-p and Crh-ser46-p Mutants With Changes In Residuesmentioning
confidence: 99%
“…The M1L mutant was expressed and purified as the wildtype protein, with similar yields [8]. The His 6 -tag was removed with thrombin.…”
Section: Mutagenesis Expression and Purification Of The Hpr 1-48 Framentioning
confidence: 99%
“…The presence of the different components of the PTS in S. coelicolor has been reported, and the corresponding proteins cloned and expressed [6,7]. We have undertaken an extensive description of the structures and conformational stabilities of the HPr and EI proteins in S. coelicolor [8][9][10][11]. HPr contains 93 amino acid residues; it lacks cysteine and tyrosine residues, and it only contains one tryptophan and one phenylalanine residues, close to the active site histidine.…”
Section: Introductionmentioning
confidence: 99%
“…All spectra were corrected by subtracting the proper baseline. The mean residue ellipticity, [H], was obtained from the raw ellipticity data, H, as reported elsewhere [10]. The helical content of scEI was calculated from its mean residue ellipticity at 222 nm [15]:…”
Section: Steady-state Measurementsmentioning
confidence: 99%
“…There is a growing interest in determining to which extent related proteins of the same family share the same conformational stability features [9]. For instance, we have shown that HPr of S. coelicolor shows different stability and folding properties than those HPrs of B. subtilis and E. coli [10,11], although the structures are similar. Stability studies of EI from E. coli [4,12] and M. capricolum [3,13] have been carried out using several spectroscopic techniques, namely, fluorescence and CD, and calorimetry (DSC).…”
Section: Introductionmentioning
confidence: 99%